γδТ-lymphocytes in patients with IgA-nephropathy - Svirskaya, Alesia V.; Nizheharodava, Darya B.; Komissarov, Kirill S.; Minchenko, Elena I.; Pilotovich, Valery S.; Zafranskaya, Marina M. (Journal of the Belarusian State University. Ecology, 2022)
Currently, IgA-nephropathy is the most common form of primary glomerulonephritis resulted in the development ofend-stage renal failure, the causes of which are not only genetic, but also environmental factors that contribute to epigeneticchanges in the both cellular and humoral immunity. The main triggers of chronic autoimmune inflammation in IgA-nephropathy are environmental factors such as industrial pollutants, infectious agents, allergens and nephrotoxic xenobioticsresulted in not only the disruption of immunoglobulin A production in mucosae but also changes in the composition ofmicrobiota and mucosal lymphoid cells, including the minor population of γδT-lymphocytes.In this study, the composition of γδT-cells subsets, their activation potential and cytotoxic activity were determined as wellas the correlation of γδT-cells immunophenotype with biochemical and histological parameters of disease progression wereestablished in patients with IgA-nephropathy. The redistribution of γδT-lymphocytes subsets in peripheral blood of patientswith IgA-nephropathy was found characterizing by a predominance of tissue-resident cells (Vδ1+ and Vδ3+T-lymphocytes) anda statistically significant decrease of Vδ2+T-cells subpopulation as compared to the control group. It was shown that γδT-lymphocytes did not demonstrate the cytotoxic activity, however, the detected increase of activated marker HLA-DR expressionon Vδ1+ and Vδ3+T-lymphocytes indicated their possible antigen-presenting role in disease pathogenesis. The obtained resultscan be used as potential biomarkers in the early diagnosis of autoimmune kidney pathology.
Keywords: IgA-nephropathy; environmental factor; epigenetics; γδT-lymphocytes; flow cytometry; autoimmune pathology